1996
DOI: 10.1182/blood.v87.12.5095.bloodjournal87125095
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of human factor IX in mice by encapsulated recombinant myoblasts: a novel approach towards allogeneic gene therapy of hemophilia B

Abstract: A potentially cost-effective strategy for gene therapy of hemophilia B is to create universal factor IX-secreting cell lines suitable for implantation into different patients. To avoid graft rejection, the implanted cells are enclosed in alginate-polylysine-alginate microcapsules that are permeable to factor IX diffusion, but impermeable to the hosts' immune mediators. This nonautologous approach was assessed by implanting encapsulated mouse myoblasts secreting human factor IX into allogeneic mice. Human facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(86 citation statements)
references
References 24 publications
5
79
1
1
Order By: Relevance
“…Cell microencapsulation has been widely applied in various therapeutic approaches including oral delivery of live bacterial cells, 1,2 production of monoclonal antibodies by immobilized hybridoma cells, 3 the development of bioartificial pancreas, 4,5 bioartificial kidney, 6 and the entrapment of cells genetically modified to secrete the desired protein in different diseases. [7][8][9][10] All of these therapeutic approaches require the use of biocompatible materials and immobilization technology to avoid cell rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Cell microencapsulation has been widely applied in various therapeutic approaches including oral delivery of live bacterial cells, 1,2 production of monoclonal antibodies by immobilized hybridoma cells, 3 the development of bioartificial pancreas, 4,5 bioartificial kidney, 6 and the entrapment of cells genetically modified to secrete the desired protein in different diseases. [7][8][9][10] All of these therapeutic approaches require the use of biocompatible materials and immobilization technology to avoid cell rejection.…”
Section: Introductionmentioning
confidence: 99%
“…While its use is inherently appealing, its success has been precluded by inconsistent performance. Alginate membranes, either alone or in conjunction with a supporting polycationic component, have been used to deliver cell therapy products for the treatment of diabetes, 1-8 chronic pain, 9 hemophilia, 10,11 central nervous system (CNS) disorders, [12][13][14][15][16][17][18][19][20][21][22] and others.…”
Section: Introductionmentioning
confidence: 99%
“…However, because C2C12 cells are a transformed cell line, there was concern about their tumourigenicity, and it was reported that they could indeed generate tumours in nude mice [26]. They are also immunogenic: encapsulated human Factor IX (hFIX)-secreting C2C12 cells were implanted into mice and hFIX could be detected in the mouse plasma up to 14 days until the appearance of anti-hFIX antibodies [15]. When the C2C12 cells were replaced by mouse foetal myoblast G8 cells which also were engineered to secret hFIX in microcapsules, there was no detectable anti-hFIX antibody until day 60 (the end of the experiment) while maintaining stable hFIX biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The cells to be encapsulated should possess several properties such as: robust proliferative potential necessary for gene transfection in vitro; capability to express and secrete the transgene product and the ability to maintain stable transgene expression after encapsulation in vitro and in vivo. Since the development of microencapsulation, many cell lines have been identified that possess these requirements and have successfully been used to deliver therapeutic proteins in different animal models [15]. In general, immortalized cell lines survive better than primary cells and are more feasible for long-term applications, whereas 'reservoirs' of primary cells are hard to maintain because of their inability to proliferate indefinitely following genetic modification.…”
mentioning
confidence: 99%